(untitled) (Bangladesh Journal of Otorhinolaryngology, 2021)
Introduction: Total laryngectomy is the gold standard treatment for advanced laryngeal cancer. Sacrifice of voice is one of the most important shortcomings of the procedure. Possibility of achieving good quality voice is greater with prosthesis compared to other method. Post laryngectomy voice rehabilitation with prosthesis yield excellent outcome in most of the cases. Swallowing, pulmonary and olfactory rehabilitation should be managed by multidisciplinary team for better quality of life (QoL). Objectives: The purpose of this study was to observe the outcomes of voice, swallowing pulmonary and olfactory rehabilitation and QoL following total laryngectomy. Methods: This cross sectional retrospective clinical study was conducted at the Head & Neck Oncology Unit, Combined Military Hospital (CMH), Dhaka. Total 57 candidates were selected. Diagnosis was done by thorough clinical examination, Fibre Optic Laryngoscopy. Contrast Enhanced Computed Tomography (CECT) scan of neck was done except few cases where MRI of neck was done for subtle cartilage erosion was suspected. Examination under anaesthesia, direct larangoscopy and biopsy was done for every cases. Candidates were post chemo-radiated/ radiated biopsy proven recurrent cases, clinically nonfunctional larynx with aspiration and radiologically evident of cartilage erosion. In all cases artificial voice prosthesis was used. All the laryngectomees underwent voice, swallowing, pulmonary and olfactory rehabilitation in laryngectomy club of head & neck oncology unit, CMH Dhaka for a period of 3 months as per standard protocol. Results: Among the 57 patients 42 of them are using voice prosthesis without any complications till to date. Voice rehabilitation started after wound healing & developed meaningful voice in around 6 weeks. Satisfactory speech & voice outcomes were observed near about 3 months. Voice quality was assessed by multivariate statistical analysis. Excellent voice was observed for 38 patients, good voice for 12 patients, fair voice for 05 patients and poor voice for 02 patients. Troubleshooting like mycotic infection developed in 6 patients which was managed by anti-fungal medication with regular appropriate cleaning, Pharyngocutaneous fistula developed in 5 patients, 3 healed later by pressure dressing and anticholinergic & 1 required exploration and flap reconstruction, 01 developed recurrent stomal stenosis which managed surgically by Y-V advancement. Prosthesis expelled out in 3 cases. 02 cases developed dysphagia due to tonicity of pharyngoesophageal (PE) segment & managed by botox injection. Significantly better voice & swallowing were reported by patients undergone laryngectomy alone in comparison with patients receiving adjuvant radiotherapy & patient undergoing salvage laryngectomy. Conclusion: Awareness should be developed as sacrifice of voice box is no more a permanent comorbidity of total laryngectomy. Excellent voice can be developed by insertion of voice prosthesis as well as swallowing pulmonary and olfactory rehabilitation following laryngectomy for better of QoL. Bangladesh J Otorhinolaryngol; April 2021; 27(1): 5-11